Meningkatkan Motivasi Belajar Siswa Melalui Pendekatan Pembelajaran Aktif (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Learning motivation is one of the important factors that influence the success of the learning process. Lack of student learning motivation often becomes an obstacle in achieving optimal learning outcomes. This article aims to examine how an active learning approach can improve student learning motivation in a formal educational environment. An active learning approach directly involves students in the learning process, either through group discussions, case studies, experiments, or simulations, thus creating a more meaningful and enjoyable learning experience. This study uses a descriptive qualitative method by collecting data from literature studies, classroom observations, and interviews with teachers and students at the junior high school level. The results of the study show that the implementation of active learning consistently can foster students' sense of responsibility for the learning process, increase self-confidence, and build a high sense of curiosity. In addition, the interaction between students and teachers becomes more dynamic, which ultimately contributes to increasing students' enthusiasm for learning. It can be concluded that active learning is not only able to increase students' intrinsic motivation but also create a more collaborative and interactive learning environment. Therefore, teachers are advised to integrate active learning strategies into the teaching process as an effort to build a productive and enjoyable learning culture. This approach is one of the effective solutions in facing the challenges of education in the modern era that demands active participation and full involvement from students.